Immunogenicity and safety of the inactivated Japanese encephalitis vaccine IXIARO® in elderly subjects: Open-label, uncontrolled, multi-center, phase 4 study. Issue 38 (31st August 2016) - Cramer, Jakob P.; Dubischar, Katrin; Eder, Susanne; Burchard, Gerd D.; Jelinek, Tomas; Jilma, Bernd; Kollaritsch, Herwig; Reisinger, Emil; Westritschnig, Kerstin
Abstract: Background: IXIARO® is a Vero cell-derived, inactivated Japanese encephalitis (JE) vaccine licensed mainly in western countries for children and adults traveling to JE endemic areas. Limited immunogenicity and safety data in elderly travelers have been available. Objectives: To evaluate safety and immunogenicity of IXIARO in elderly subjects. Methods: Open-label, single arm, multi-centered study. Two-hundred subjects with good general health, including adequately controlled chronic conditions, received two doses of IXIARO®, 28 days apart. Protective levels of antibodies were tested 42 days after the second dose. Systemic and local adverse events (AEs) were solicited for 7 days after each dose, unsolicited AEs were collected up to day 70 and in a phone call at month 7. Summary of results: Subjects were aged 64–83 years (median 69.0 years). Nineteen percent of subjects had serious or medically attended AEs up to Day 70 (primary endpoint), none of them causally linked to IXIARO. Solicited local AEs were reported by 33.5% (most common: local tenderness) and solicited systemic AEs by 27% (most common: headache) of subjects. The seroprotection rate was 65% with a geometric mean titre (GMT) of 37. Subjects with tick borne encephalitis (TBE) vaccinations in the past 5 years ( N = 29) had a SCR of 90% and GMT of 65. Conclusions: IXIARO is generally well tolerated in the elderly, and the safety profile is largely comparable with younger adults. SCR and GMT are lower compared to younger adults, but SCR is in the range reported in elderly for other vaccines e.g. against TBE, hepatitis-A virus (HAV)/hepatitis-B virus (HBV), influenza. The differences in SCR and GMT from younger to elderly adults were in the range of other vaccines. Duration of protection is uncertain in older persons, therefore a booster dose (third dose) should be considered before any further exposure to JE virus.